الاحتياجات التدريبية وفق التدريس بالمقاربة بالكفاءات دراسة ميدانية لطلبة المدرسة العليا للأساتذة بالقبة - بالقاسمي, شعبان (University of Eloued جامعة الوادي, 2016)
هدفت هذه الدراسة إلى محاولة معرفة درجة الاحتياجات التدريبية للأستاذ المتكون في المدرسة العليا للأساتذة بالقبة وفق التدريس بالكفاءات على مستوى كل من التخطيط، والتنفيذ، والتقويم. حيث تم إجراء هذه الدراسة على (135) طالبا متكون بالمدرسة العليا للأساتذة بالقبة، وللتأكد من صحة هذه الفرضيات تم اختيار المنهج الوصفي التحليلي الملائم لطبيعة الدراسة، كما استعملنا الأداة المتمثلة في الاستبيان حول الاحتياجات التدريبية للأستاذ وفق التدريس بالمقاربة بالكفاءات المحضر للدراسة. وقد توصلت الدراسة إلى أن معظم أفراد العينة لديهم احتياجات تدريبية تقدم بمتوسط حسابي نسبته 1.81، كما تبين وجود احتياجات تدريبية في مرحلة التخطيط بمتوسط حسابي 1.9، أما على مستوى التنفيذ فالمتوسط الحسابي قد بلغ 1.72، كما بلغ المتوسط الحسابي للتقويم 1.83، وقد أشارت هذه النتائج أن جميع مراحل التدريس بالكفاءات لديها درجة متوسطة تؤكد على وجود الاحتياجات التدريبية للطالب المتكون على مستوى المدرسة العليا للأساتذة وفق التدريس بالمقاربة بالكفاءات، مما يدل على أن جميع الفرضيات قد تحققت واختتمت الدراسة بخلاصة. This study aimed to try and find out the degree of professor training needs component in graduate school professors according to the teaching competencies at the level of each of the planning, implementation, and evaluation. The study was conducted to (135) created high school students to professors. To ensure the validity of these assumptions, we chose descriptive analytical method that is appropriate to the nature of the study. Also, we used a tool of the questionnaire administered to the professor training needs in accordance with the teaching competencies record proactive approach. The study found that most respondents have training needs provides a means rate of 1.81, The existence of training needs in the planning stage also shows a means of 1.9. At the level of implementation in the arithmetic average has reached 1.72. The arithmetic average of the calendar reached 1.83. These results indicate that all stages of the teaching competencies have a medium to confirm the presence of the students formed the training needs of the Higher School of professors teaching proactive approach according to the level of competencies which indicates that all hypotheses have been confirmed and the study concludes with a summary.
Proactive approach in accordance with the teaching competencies training needs A field study for students of the Higher School of professors dome
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الاحتياجات التدريبية، المقاربة بالكفاءات; Training Needs, Approach competencies